2024
DOI: 10.1200/po.23.00453
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risks Associated With TP53 Pathogenic Variants: Maximum Likelihood Analysis of Extended Pedigrees for Diagnosis of First Cancers Beyond the Li-Fraumeni Syndrome Spectrum

Cristina Fortuno,
Bing-Jian Feng,
Courtney Carroll
et al.

Abstract: PURPOSE Establishing accurate age-related penetrance figures for the broad range of cancer types that occur in individuals harboring a pathogenic germline variant in the TP53 gene is essential to determine the most effective clinical management strategies. These figures also permit optimal use of cosegregation data for classification of TP53 variants of unknown significance. Penetrance estimation can easily be affected by bias from ascertainment criteria, an issue not commonly addressed by previous studies. MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…Specifically, (1) half of their families were from Australian resources that focused on hereditary cancers, especially breast cancer (they did not mention the selection criteria for the families from Spain and the United States), and (2) all family members' phenotypes were used in the adjustment for ascertainment in their statistical analysis. Considering previous studies, the same pattern is also observed: The risk estimate from women unselected for breast cancer family history 3 is consistent with our estimate, whereas the risk estimates from Li-Fraumeni Syndrome families 4,5 are consistent with those of Fortuno et al 1 From an etiological perspective, the existence of a risk difference between members of high-risk families and members of unselected families implies that breast cancer risk associated with TP53 PVs, or the PVs themselves, is inherently different for these two populations, and/or the risks are modified by other factors shared within families, genetic, or environmental. Such potential differences and/or modifications have also been observed for carriers of PVs in other breast cancer susceptibility genes such as BRCA1, BRCA2, and PALB2.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, (1) half of their families were from Australian resources that focused on hereditary cancers, especially breast cancer (they did not mention the selection criteria for the families from Spain and the United States), and (2) all family members' phenotypes were used in the adjustment for ascertainment in their statistical analysis. Considering previous studies, the same pattern is also observed: The risk estimate from women unselected for breast cancer family history 3 is consistent with our estimate, whereas the risk estimates from Li-Fraumeni Syndrome families 4,5 are consistent with those of Fortuno et al 1 From an etiological perspective, the existence of a risk difference between members of high-risk families and members of unselected families implies that breast cancer risk associated with TP53 PVs, or the PVs themselves, is inherently different for these two populations, and/or the risks are modified by other factors shared within families, genetic, or environmental. Such potential differences and/or modifications have also been observed for carriers of PVs in other breast cancer susceptibility genes such as BRCA1, BRCA2, and PALB2.…”
supporting
confidence: 92%
“…This could be misleading, especially for the public without relevant knowledge and for clinicians who are not aware of the complexity related to penetrance interpretation. We believe that the relevance of the risk estimates, both Fortuno's and ours, should be emphasized so that women with different circumstances can be advised about the most relevant risk estimate, and the dedicated breast screening for women from a young age, as suggested by Fortuno et al, 1 No potential conflicts of interest were reported.…”
mentioning
confidence: 72%
See 1 more Smart Citation